FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PENAWARAN UMUM PERDANA DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Inten Palupi, 13.05.52.0180; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of underwriterâs reputation, corporate profitability (ROA), financial leverage (DER), firmâs scale and firmâs age on the level of underpricing with the case study companies on the Stock Exchange Indonesia periode from 2012 to 2015. The research used purposive sampling method . Secondary datas were used and obtained from the Indonesian Stock Exchange by using Multiple Regression analysis testing to prove the researchâs hypothesis. The results shows that the underwriters reputation, corporate profitability (ROA), and financial leverage (DER) affected the underpricing negatively. The scale of companies affected on the level of underpricing positively and the firmâs age do not significantly affected the level of underpricing.Keywords: Underpricing, Underwriterâs Reputation, Corporate Profitability (ROA), Financial Leverage (DER), Firmâs Scale and Firmâs Age